Using multi-objective optimization to secure fertile soils across municipalities - Schwaab, Jonas; Lautenbach, Sven; Strien, Maarten Jan van; Grêt-Regamey, Adrienne (Applied geography, 2018)
To protect fertile agricultural land and guarantee food security in regions that are strongly affected by urban growth, it is crucial to use and design appropriate policy instruments. In Switzerland, as well as in many other countries worldwide, one of the most important instruments for steering urban development is zoning. Zoning regulations are usually implemented at local governance levels (i.e. at municipality level) and have proven to effectively account for externalities. To determine whether zoning across municipalities could lead to a better protection of fertile agricultural soils, we developed an innovative approach based on multi-objective optimization. Using this approach we quantified the trade-off between reducing the loss of agricultural productivity and obtaining compact urban development patterns. We show that cooperation between municipalities is useful at two different stages in the decision-making process. Firstly, municipalities should cooperate when they define their environmental and socio-economic development goals and rank their preferences concerning different goals. Secondly, municipalities should cooperate when deciding on how much agricultural land should be converted into urban land. These results allow decision-makers to understand if zoning at a supra-municipal level significantly reduces the loss of agricultural productivity and should thus be favoured over zoning at the municipal level.